2019
DOI: 10.1038/s41598-019-53593-5
|View full text |Cite
|
Sign up to set email alerts
|

CgSTE11 mediates cross tolerance to multiple environmental stressors in Candida glabrata

Abstract: Candida glabrata is a human commensal and an opportunistic human fungal pathogen. It is more closely related to the model yeast Saccharomyces cerevisiae than other Candida spp. Compared with S. cerevisiae, C. glabrata exhibits higher innate tolerance to various environmental stressors, including hyperthermal stress. Here we investigate the molecular mechanisms of C. glabrata adaptation to heat stress via adaptive laboratory evolution. We show that all parallel evolved populations readily adapt to hyperthermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…The mechanism of acid stress tolerance in C. glabrata has not been extensively investigated. The low pH of C. glabrata cultures during pyruvate production causes a slow or total halt in growth due to acid accumulation [64,65]. Contrary to the view of Yan et al [66] that overexpression of the transcription factor CgCrz1p enhances viability, cellular biomass, and pyruvate yields at a low pH.…”
Section: Adaptation To Various Environmental Conditionsmentioning
confidence: 92%
“…The mechanism of acid stress tolerance in C. glabrata has not been extensively investigated. The low pH of C. glabrata cultures during pyruvate production causes a slow or total halt in growth due to acid accumulation [64,65]. Contrary to the view of Yan et al [66] that overexpression of the transcription factor CgCrz1p enhances viability, cellular biomass, and pyruvate yields at a low pH.…”
Section: Adaptation To Various Environmental Conditionsmentioning
confidence: 92%
“…Similarly, short-term adaptation of the eukaryotic microorganism Rhodotorula mucilaginosa at 40°C for 30 min not only increased high temperature tolerance, but also enhanced tolerance to H 2 O 2 , NaCl and high heat stress, and the survival rate of their cells increased about 1.2-fold ( Cheng et al, 2016 ). It was also found that Candida glabrata , an opportunistic fungal pathogen, was also adapted at high temperatures to enhance tolerance to other environmental stresses ( Roetzer et al, 2011 ; Huang et al, 2019 ).…”
Section: Mechanisms Of Adaptationmentioning
confidence: 99%
“…After high-temperature adaptation of C. glabrata , the strains screened showed convergence in evolutionary phenotypes and the mutation in CgSTE11 was found to play a major role in high-temperature tolerance and in the observed cross-stress to other environmental stressors ( Huang et al, 2019 ). The CgSTE11 mutation was also significantly more resistant to heat and acetic acid ( Huang et al, 2019 ). It can be seen that mutations in genes affect the stress tolerance of microorganisms.…”
Section: Mechanisms Of Adaptationmentioning
confidence: 99%
“…For example, CgSTE11 of C . glabrata plays an important role in high temperature tolerance and broad cross-tolerance to other environmental stresses, including acids, alcohol, and oxidants (Huang et al 2019a ). We previously showed that there are cross-linkages between regulatory elements, signaling pathways, and transcription factors, in the resistance to various stresses (Song et al 2016 ; Xin et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%